Cenozoic tectonic subsidence characteristics of Albert Lake Depression in East African Rift System - Chenyu Zheng; Hongyan Zhao; Chunguang Qiu; Yaoyao Zou; Liang Wang; Bin Hu; Shen Jia; Chuanbo Shen (地质科技通报, 2021)
The Cenozoic East African Rift is a typical intracontinental rift at the germination stage of the Wilson cycle, which has long attracted the attention of geologists at home and overseas. The Albert Lake Depression is located at the northern most end of the west branch of the East African Rift System.It is an asymmetric (half) graben with a NW orientation. At present, good industrial oil and gas have been discovered in this area.The analysis of the subsidence evolution is of great significance to further reveal the tectonic subsidence characteristics and petroleum exploration potential of this depression.Based on drilling data, combined with seismic interpretation, and analysis of subsidence history, burial history and fault activities, this paper reclassifies tectonic units, and summarizes the characteristics of tectonic subsidence. The relationship between subsidence and fault activities, the law of subsidence center migration and its indicating significance for petroleum exploration were discussed in this study. The results show that the secondary structural units in the east of the Albert Lake Depression are mainly controlled by the eastern boundary faults, and the F1 and F2 faults play a major role in controlling the subsidence and formation of the eastern steep fault belt, the eastern fault terrace zone and the three structural adjustment belts. The subsidence rate of the southern sub sag was large in the early stage, which was conducive to the formation of extremely thick source rocks in Late Miocene.With the northward migration of the subsidence center, the Upper Miocene and Lower Pliocene source rocks were developed in the northern sub sag.The structural belt around the subsidence center is the favorable direction area for hydrocarbon migration and accumulation. This study provides a new basis for further petroleum in Albert Lake Depression of the East African Rift System.